2022
DOI: 10.3389/fphy.2022.809133
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Tissue Microstructure Using Tensor-Valued Diffusion Encoding: Brain and Body

Abstract: Diffusion-weighted magnetic resonance imaging (DW-MRI) is a non-invasive technique to probe tissue microstructure. Conventional Stejskal–Tanner diffusion encoding (i.e., encoding along a single axis), is unable to disentangle different microstructural features within a voxel; If a voxel contains microcompartments that vary in more than one attribute (e.g., size, shape, orientation), it can be difficult to quantify one of those attributes in isolation using Stejskal–Tanner diffusion encoding. Multidimensional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 163 publications
(255 reference statements)
0
5
0
Order By: Relevance
“…DTI metrics are sensitive but not specific. We expected features exclusive to B-Tensor encoding to improve the classification algorithm by providing additional information, given their specificity to certain properties of microstructure [8]. For instance, we expected C c to capture the increased axonal dispersion typical of WM degeneration, as previous studies using standard DW-MRI acquisitions had suggested [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DTI metrics are sensitive but not specific. We expected features exclusive to B-Tensor encoding to improve the classification algorithm by providing additional information, given their specificity to certain properties of microstructure [8]. For instance, we expected C c to capture the increased axonal dispersion typical of WM degeneration, as previous studies using standard DW-MRI acquisitions had suggested [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MDE DW-MRI can potentially characterize certain neuropathological changes in detail. However, relatively few studies have used this technique for this purpose [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been interest in going beyond SDE with double (planar) or triple (spherical) diffusion encoding, which can help disentangle features of various microstructure compartments (like orientation dispersion) within a voxel (Afzali et al, 2022). (Basser et al, 1994), Diffusion Kurtosis Imaging (DKI) (Jensen et al, 2005), and the Q-ball method (Tuch, 2004).…”
Section: Diffusion Mri Modelsmentioning
confidence: 99%
“…Hence, DTI metrics are sensitive but not specific. We expected features exclusive to b-tensor encoding to improve the classification algorithm by providing additional information, given their specificity to certain properties of microstructure [11]. In this light, C c should capture the increased axonal dispersion characteristic of white matter degeneration [54], while μFA would inform of the reduction of microscopic anisotropy.…”
Section: Plos Onementioning
confidence: 99%
“…Thus, MDE DW-MRI potentially describes neuropathological changes in detail. However, relatively few studies have used this technique for this purpose [11,12].…”
Section: Introductionmentioning
confidence: 99%